Influence Of Personal Preferred Creative Problem-Solving Style And Organisational Creativity Factors On Types Of Lateral Thinking - Ow, Alex Chee Kin (2009)

(untitled)
There were numerous studies on creative thinking especially on individual creativity but not on the types of lateral thinking. In this research, the general objective was to develop a multi-dimensional model of organisational creativity and developed instruments to measure the majority of the factors in the model. The specific objectives were to examine the influence of personal preferred style in creative problem solving and organisational creativity factors on the types of lateral thinking. This study also aimed to explore to what extent the types of lateral thinking could affect the decision outcomes.The research methodology used was a quantitative survey to test the theory that was hypothesized in the research framework. It involved 217 people across all departments at the supervisory, executive and managerial level from a sample of ten (10) organisations in Malaysia that has undergone creativity training by the researcher from the year 2000 to year 2004. Four (4) instruments were administered by the researcher namely Creative Process Inventory (CPI), Organisational Creativity Factors (OCF), Lateral Thinking Test (LTT) and Decision Making Outcomes (DMO). The research indicated that personal preferred styles have no significant impact on the explanation of observed variances in the types of lateral thinking. However, the organisational creativity factors showed a significant association with a chi-square value of 30.61. This explained that there could be other factors that influenced the types of lateral thinking. The three variables that are significant predictors of novelty ideas were creativity training, idea implementation process and idea assessment process. The model explained that the overall predictive accuracy was 68.2% of the types of lateral thinking, thus presenting a relatively good model of exogenous variables. Overall, the model correctly predicted 80.3% of the cases for novelty ideas and 52.6% for predicting effective ideas. The recommendations for organisations were to train their executives in creative thinking, applications of effective ideas and a chance in leading a problem solving session, setting up creativity assessment and implementation policies. The recommendations for future research were to identify other factors that may affect individual’s preferred styles, types of lateral thinking, and how these affect the decision outcomes.